Design and implementation of carry Look ahead generator in reversible logic using nano QCA. Issue 1 (February 2021) - Kannaki, S; Karthigai Lakshmi, S; Jaganathan, S; Sujatha, C; Bhoopesh, D; Balaji, S
Abstract: The idea of reversible logic is another emerging architecture that has developed its ground in research area. This argument implied zero heat dissipation at the device. According to the physical laws of quantum mechanical effect and the law of coulomb the function and heat relations are satisfied. In this paper, a carry-looking generator is built using reversible logic and its QCA have been reported. To achieve the proposed design use was made of Toffoli and BJN gate. Comparing simulation outcomes to theoretical values verifies the design. The proposed model is tested and simulated using version 2.0.3 of the QCA Designer method.